Influence of the international context on the signing of the Dominican-Spanish recognition treaty in 1855 - Escolano Giménez, Luis Alfonso (Hispania Nova, 2021)
The period around the recognition treaty between Spain and the Dominican Republic in 1855 is essential to study the causes of foreign intervention in the Caribbean country, since it reveals both the internal and external dynamics that led to serious instability arising from the struggles among local groups that were supported by different countries with their own goals. Under the pretext of mediating between Haitians and Dominicans, the main powers vied to increase their influence over the Santo Domingo executive, initially by establishing diplomatic relations. Although the first initiatives of the Dominican government to reach an agreement with Spain were rejected by the Madrid cabinet, it eventually decided to establish relations with that of Santo Domingo in order to act on the ground and hinder U.S. expansionism in the Dominican Republic, since the Spanish authorities in Cuba and Puerto Rico considered it a threat to the preservation of these islands.
Keywords: international relations (19th century); Dominican Republic; U.S. expansionism; foreign interference; Dominican-Spanish relations; foreign Spanish policy